2015
DOI: 10.1007/s11695-015-1622-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Use of Covered Self-Expandable Endoscopic Stent on the Treatment of Postoperative Stapler Line Leaks

Abstract: SEES is a feasible, safe, and effective management of post BS leaks, although patients may also require prosthesis revision and abdominal exploration. Primary SEES placement is associated with a shorter leak resolution time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Despite the novel double-bump structure of the Beta stent, which has specifically been designed to prevent migration, migration occurred in 32% of patients (26% of stents) in this study. This seems comparable to the results of other fully covered stents, with a migration rate of 18–67% in previous studies [8, 11, 16, 17, 19, 20]. Partially covered stents are less prone to migration with a migration rate of 5–15% [7, 10, 14, 15, 18].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the novel double-bump structure of the Beta stent, which has specifically been designed to prevent migration, migration occurred in 32% of patients (26% of stents) in this study. This seems comparable to the results of other fully covered stents, with a migration rate of 18–67% in previous studies [8, 11, 16, 17, 19, 20]. Partially covered stents are less prone to migration with a migration rate of 5–15% [7, 10, 14, 15, 18].…”
Section: Discussionsupporting
confidence: 88%
“…Gastric leaks after laparoscopic sleeve gastrectomy (LSG) have proven to be a disastrous complication resulting in longer hospital stays and the need to use a number of modalities for rescue [1][2][3][4][5][6]. The LSG procedure has flourished [7,8], bringing about the decline of leak rates from the procedure while making the resolution of such leaks a larger concern for all surgeons dealing with LSG patients during the postoperative period.…”
mentioning
confidence: 99%
“…Options for management-including reoperation [1,3,4,9,10], endoscopic management with clips or stents [5,6,11], Over-Stitch [12], and other modalities [13,14]-have had good outcomes. There has been no evidence in the literature of use of endoluminal vacuum (E-Vac) therapy for LSG leaks; however, E-Vac therapy has been used with good results for a variety of foregut leaks and perforations, and in some cases, better results than with the use of stents [15][16][17][18][19].…”
mentioning
confidence: 99%
“…The duration of stent treatment has not been standardized, but 6–8 weeks appears to be the optimal time for stent removal because a shorter interval leads to incomplete leak closure and a longer interval may lead to stent migration or mucosal hypertrophy associated with increased difficulty of stent extraction [9]. Earlier stent treatment has been found to be associated with increased success and shorter healing time [14–17]. We also found that successful removal of the stent as early as 3 weeks after stent placement was achieved in three patients who experienced only a small leak.…”
Section: Discussionmentioning
confidence: 82%